2014
DOI: 10.1111/j.2047-2927.2014.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

AR and SRD5A2 gene mutations in a series of 51 Turkish 46,XY DSD children with a clinical diagnosis of androgen insensitivity

Abstract: SUMMARY46,XY disorders of sex development (DSD) are caused by disorders of gonadal development, androgen biosynthesis and receptor (AR) defects. Although, clinical/biochemical features help in distinguishing specific aetiologies, there are overlaps which necessitate molecular analyses for the definitive diagnosis. To test precision of our clinical diagnosis of androgen insensitivity (AIS) by analysing AR and then SRD5A2 genes, patients were recruited at Marmara University Hospital and molecular analyses were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 46 publications
(57 reference statements)
2
31
1
1
Order By: Relevance
“…At birth, these people are either diagnosed with the enzyme deficiency or misdiagnosed with androgen insensitivity syndrome [5]. However, certain genotypically male infants are born completely undervirilized and appear phenotypically female.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At birth, these people are either diagnosed with the enzyme deficiency or misdiagnosed with androgen insensitivity syndrome [5]. However, certain genotypically male infants are born completely undervirilized and appear phenotypically female.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen receptors must be present and responsive to DHT and testosterone in order for external sexual characteristics to take effect. A defect in any of the previously mentioned enzymes or hormone receptors could lead to discordance between genotype and phenotype [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This substitution was previously reported in several 5α-reductase-2 deficiency patients of various ethnic origin including Italy, Turkey, UK, Sweden, USA (GreekAmericans), Brazil (with European origin), Cote d'Ivoire, and India [Carpenter et al, 1990;Thigpen et al, 1992;Sinnecker et al, 1996;Nordenskjöld and Ivarsson, 1998;Hackel et al, 2005;Nicoletti et al, 2005;Baldinotti et al, 2008;Nagaraja et al, 2010, Berra at al., 2011Maimoun et al, 2011;Akcay et al, 2014]. The wide spreading of p.G196S in different ethnic groups suggests a recurrence of the mutation and a possible hot spot in SRD5A2 or a common ancestor a long time ago in human evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Through the chi-square test, there was no statistical difference between experimental and control groups. Other research has found that c.265C > G and p.L89V mutations were related to sperm quality (Massanyi et al, 2013), severe hypospadias (Akcay et al, 2014), and prostate cancer risk (Gottlieb et al, 2012).…”
Section: Discussionmentioning
confidence: 99%